The grit beneath the glitter : tales from the real Las Vegas - Rothman, Hal, 1958-2007; Davis, Mike, 1946- (University of California Press, 2002)
The Grit Beneath the Glitter is the first real look at the new Las Vegas from the inside. In it, long-time residents as well as professionals reflect on the transformation of one of the fastest-growing and most famous cities on earth, yet one about which relatively little is known.